Genomic and Biochemical Analysis of the Diaminopimelate and Lysine Biosynthesis Pathway in Verrucomicrobium spinosum: Identification and Partial Characterization of L,L-Diaminopimelate Aminotransferase and UDP-N-Acetylmuramoylalanyl-D-glutamyl-2,6-meso-Diaminopimelate Ligase - Nachar, Victoria R.; Savka, Francisco C.; McGroty, Sean E.; Donovan, Katherine A.; Dobson, Renwick C.; North, Rachel A.; Buckley, Larry J.; Hudson, Andre O. (Frontiers in Microbiology, 2012)
The Gram-negative bacterium Verrucomicrobium spinosum has attracted interest in recent years following the sequencing and annotation of its genome. Comparative genomic analysis of V. spinosum using diaminopimelate/lysine metabolic genes from Chlamydia trachomatis suggests that V. spinosum employs the L,L-diaminopimelate aminotransferase (DapL) pathway for diaminopimelate/lysine biosynthesis. The open reading frame corresponding to the putative dapL ortholog was cloned and the recombinant enzyme was shown to possess L,L-diaminopimelate aminotransferase activity in vitro. In vivo analysis using functional complementation confirmed that the dapL ortholog was able to functionally complement an E. coli mutant that confers auxotrophy for diaminopimelate and lysine. In addition to its role in lysine biosynthesis, the intermediate diaminopimelate has an integral role in peptidoglycan biosynthesis. To this end, the UDP-N-acetylmuramoylalanyl-D-glutamyl-2, 6-meso-diaminopimelate ligase ortholog was also identified, cloned and was shown to possess meso-diaminopimelate ligase activity in vivo. The L,L-diaminopimelate aminotransferase pathway has been experimentally confirmed in several bacteria, some of which are deemed pathogenic to animals. Since animals, and particularly humans, lack the genetic machinery for the synthesis of diaminopimelate/lysine de novo, the enzymes involved in this pathway are attractive targets for development of antibiotics. Whether dapL is an essential gene in any bacteria is currently not known. V. spinosum is an excellent candidate to investigate the essentiality of dapL, since the bacterium employs the DapL pathway for lysine and cell wall biosynthesis, is non-pathogenic to humans, facile to grow and can be genetically manipulated.